Antioxidant and antibacterial activity of Aloe vera gel extracts. - Saritha, V (International Journal of Pharmaceutical & Biological Archive, 2010)
The antioxidative properties of extracts of Aloe vera gel made in methanol (MEAG), 95% ethanol (EEAG), hexane (HEAG), acetone (AEAG) and chloroform (CEAG) were investigated employing various in vitro systems viz. 1, 1-diphenyl-2-picrylhydrazyl (DPPH), superoxide anion radicals scavenging, metal ion chelation, reducing power, hydroxyl radicals scavenging and total antioxidant activity in linoleic acid emulsion system. The results showed that MEAG and AEAG possessed maximum DPPH free radical and superoxide radical scavenging activities. All the extracts were effective in scavenging the hydroxyl radicals in nonsite-specific assay as well as in site specific assay. The formation of the Ferrozine- Fe2+ complex was found to be incomplete in the presence of MEAG and AEAG, indicating their capacity in chelating iron. The AEAG was shown more reducing power than MEAG. The in vitro antibacterial properties of methanolic extract of Aloe vera gel extract were investigated against various common pathogenic bacteria. The gel extract showed significant zone of inhibition against all the pathogens studied and the results were comparable to the conventional antibiotics. Hence it is suggested that Aloe vera gel extract could be same as a new source of natural antioxidant with potential applications for reducing the levels of lipid oxidation and oxidative stress.